2009
DOI: 10.3748/wjg.15.3276
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fecal incontinence on quality of life

Abstract: AIM:To explore the impact of fecal incontinence (FI) on quality of life (QOL) of patients attending urogynecology and colorectal clinics (CCs). METHODS:Cross-sectional study of 154 patients (27 male) with FI, who attended the clinics at a regional hospital in North Queensland, Australia in 2003 and2004, and completed the Fecal Incontinence Quality of Life Scale (FIQL: 1 = very affected; 4 = not affected). RESULTS:More than 22% of patients had their QOL affected severely by FI. Patients reported that they had n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
76
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 33 publications
0
76
2
3
Order By: Relevance
“…Our results are consistent with those of Alsheik et al, 7 although in that study all four FIQL subscales were combined, and partially with Cohan's, 32 who found male gender to be significantly associated with improved coping and embarrassment scores. However, other studies did not find significant differences between the sexes 30 or reported an improved life style scoring associated with being female. 31 Differences in impact on QoL in women versus men might be explained by different social expectations, as personal image has traditionally been considered more important for women.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Our results are consistent with those of Alsheik et al, 7 although in that study all four FIQL subscales were combined, and partially with Cohan's, 32 who found male gender to be significantly associated with improved coping and embarrassment scores. However, other studies did not find significant differences between the sexes 30 or reported an improved life style scoring associated with being female. 31 Differences in impact on QoL in women versus men might be explained by different social expectations, as personal image has traditionally been considered more important for women.…”
Section: Discussionmentioning
confidence: 84%
“…Although QoL for patients with fecal incontinence has been researched, little has been said about the impact of gender. Few studies of community-dwelling patients have tried to explore this aspect and results have varied: one study did not find differences between genders, 30 another found slightly better QoL in women, 31 in a third, higher coping and embarrassment scores were associated with men, 32 and a fourth study 7 reported that women had a significantly lower average QoL; in this latter study, however, the FIQL dimensions most affected were not specified. Knowledge of how gender affects QoL can be of great importance when treating and counseling patients.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…[34][35][36] The occurrence of incontinence episodes less than once a month is reported to have a lower impact on QoL than more frequent incontinence episodes; however, one study found monthly and weekly episodes of stool incontinence to be equally distressing for patients with long-standing AI. 35 In contrast to previous reports of flatus incontinence at any frequency being the least bothersome symptom of AI 31 , the findings in this study suggest that experiencing flatus incontinence alone on a weekly or daily basis has a profound negative impact on QoL, especially in the domain 'Embarrassment'. In a previous study, persistent AI symptoms in the first 2 years postpartum were found to negatively affect QoL, and severe symptoms affected QoL more than less severe symptoms did.…”
Section: Discussionmentioning
confidence: 99%
“…FI can lead to social isolation. It also can adversely affect ability to maintain relationships, occupation and self-esteem aspects of the quality of life (QOL) [10,11] . Ulcerative colitis (UC) and Crohn's disease (CD) are chronic inflammatory conditions related to the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%